Development of a Large Animal Model of Osteochondritis Dissecans of the Knee: A Pilot Study. Issue 2 (16th February 2015) - Pfeifer, Christian G.; Kinsella, Stuart D.; Milby, Andrew H.; Fisher, Matthew B.; Belkin, Nicole S.; Mauck, Robert L.; Carey, James L.
Background: Treatment of osteochondritis dissecans (OCD) of the knee is challenging, and evidence for stage-dependent treatment options is lacking. Basic science approaches utilizing animal models have provided insight into the etiology of OCD but have yet to produce a reliable and reproducible large animal model of the disease on which to test new surgical strategies. Purpose/Hypotheses: The purpose of this study was to develop an animal model featuring an OCD-like lesion in terms of size, location, and International Cartilage Repair Society (ICRS) grading. The hypothesis was that surgical creation of an osteochondral defect followed by placement of a barrier between parent bone and progeny fragment would generate a reproducible OCD-like lesion. Study Design: Controlled laboratory study. Methods: Bilateral osteochondral lesions were created in the medial femoral condyles of 9 Yucatan minipigs. After lesion creation, a biodegradable membrane was interposed between the progeny and parent bone. Five different treatment groups were evaluated at 2 weeks: a control with no membrane (ctrl group; n = 4), a slowly degrading nanofibrous poly(∊-caprolactone) membrane (PCL group; n = 4), a fenestrated PCL membrane with 1.5-mm holes covering 25% of surface area (fenPCL group; n = 4), a collagen membrane (Bio-Gide) (CM group; n = 3), and a fenestrated CM (fenCM group; n = 3). Five unperturbed lateral condyles (1 from each treatment group) served as sham controls. After euthanasia on day 14, the lesion was evaluated by gross inspection, fluoroscopy, micro–computed tomography (micro-CT), and histology. To quantify changes between groups, a scoring system based on gross appearance (0-2), fluoroscopy (0-2), and micro-CT (0-6) was established. Micro-CT was used to quantify bone volume per total volume (BV/TV) in a defined region surrounding and inclusive of the defect. Results: The no scaffold group showed healing of the subchondral bone at 2 weeks, with continuity of subchondral bone elements. Conversely, condyles treated with PCL or CM showed substantial remodeling, with loss of bone in both the progeny fragment and surrounding parent bone. When these membranes were fenestrated (fenPCL and fenCM groups), bone loss was less severe. Histological analysis showed no integration in the cartilage layer in any treatment group, while fibrous tissue formed between the parent and progeny fragments. Micro-CT showed significant differences in mean BV/TV between the PCL (27.4% ± 2.3%) and the sham (47.7% ± 1.4%) or no scaffold (54.9% ± 15.1%) groups ( P < .01 and P < .05, respectively). In addition, a significant difference in bone loss was evident between the PCL and fenPCL groups (mean BV/TV, 46.6% ± 15.2%; P < .05), as well as between the PCL and fenCM (mean BV/TV, 50.9% ± 3.5%) and fenPCL groups ( P < .01). Grading by 6 blinded reviewers using an OCD scoring system with 3 subcategories showed a significant difference between control and PCL groups. Conclusion: This study successfully developed a large animal model of OCD-like lesions in the knee joint of Yucatan minipigs. The lesions generated matched characteristics of an ICRS grade 3 OCD lesion in humans. These findings set the stage for ongoing model refinement as well as exploration of novel interventional therapies to restore function and bone and cartilage patency in individuals affected by this rare but significant disease. Clinical Relevance: This developed model will serve as a platform on which to further investigate the natural course as well as emerging treatment options for OCD.